Report of the Third Asean-Japan Workshop-Cum-Seminar on Urban Transportation 1996, 13-15 November 1996, The Regent Kuala Lumpur, Malaysia - Malaysia. Kementerian Pengangkutan; Asean-Japan Workshop-Cum-Seminar on Urban Transportation (3rd : 1996 : The Regent Kuala Lumpur, Malaysia) ([s.l. : s.n.], 1996)
08